A simple clinical coding strategy to improve recording of child maltreatment concerns: an audit study. Issue 1 (1st January 2015) - McGovern, Andrew; Woodman, Jenny; Allister, Janice; van Vlymen, Jeremy; Liyanage, Harshana; Jones, Simon; Rafi, Imran; de Lusignan, Simon; Gilbert, Ruth
Abstract : Background: Recording concerns about child maltreatment, including minor concerns, is recommended by the General Medical Council (GMC) and National Institute for Health and Clinical Excellence (NICE) but there is evidence of substantial under-recording. Aim: To determine whether a simple coding strategy improved recording of maltreatment-related concerns in electronic primary care records. Design and Setting: Clinical audit of rates of maltreatment-related coding before January 2010–December 2011 and after January–December 2012 implementation of a simple coding strategy in 11 English family practices. The strategy included encouraging general practitioners to use, always and as a minimum, the Read code 'Child is cause for concern'. A total of 25, 106 children aged 0–18 years were registered with these practices. We also undertook a qualitative service evaluation to investigate barriers to recording. Method: Outcomes were recording of 1) any maltreatment-related codes, 2) child protection proceedings and 3) child was a cause for concern. Results: We found increased recording of any maltreatment-related code (rate ratio 1.4; 95% CI 1.1–1.6), child protection procedures (RR 1.4; 95% CI 1.1–1.6) and cause for concern (RR 2.5; 95% CI 1.8–3.4) after implementation of the coding strategy. Clinicians cited the simplicity of the coding strategy as the most important factor assisting implementation. Conclusion: This simple coding strategy improved clinician's recording of maltreatment-related concerns in a small sample of practices with some 'buy-in'. Further research should investigate how recording can best support the doctor–patient relationship. How this fits in: Recording concerns about child maltreatment, including minor concerns, is recommended by the General Medical Council (GMC) and National Institute for Health and Clinical Excellence (NICE), but there is evidence of substantial underrecording. We describe a simple clinical coding strategy that helped general practitioners to improve recording of maltreatment-related concerns. These improvements could improve case finding of children at risk and information sharing.